ПРЕДПОСЫЛКИ СОЗДАНИЯ КОНЦЕПЦИИ ИНФОРМАЦИОННОЙ ВОЙНЫ В ЭРУ НОВЕЙШИХ ТЕХНОЛОГИЙ - Oleksandr V. Voitko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni, 2013)
Tendencies and prospects of development of the concept of information warfare on the analysis and experience of modern local wars and armed conflicts are considered.